2017
DOI: 10.11138/mltj/2017.7.1.192
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measures of tendon thickness: Intra-rater, Inter-rater and Inter-machine reliability

Abstract: SummaryBackground: Ultrasound imaging is often used by physiotherapists and other healthcare professionals but the reliability of image acquisition with different ultrasound machines is unknown. The objective was to compare the intra-rater, inter-rater and intermachine reliability of thickness measurements of the plantar fascia (PF), Achilles tendon (AT), patellar tendon (PT) and elbow common extensor tendon (ECET) with musculoskeletal ultrasound imaging (MSUS). KEY WORDS: quantitative ultrasound, reliability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…Ultrasound is the commonest examination for tendons and it considers primary three tendon features: (i) Thickness—tendinopathy can cause an increase in tendon thickness, due to a change in the number and type of cells of the tendon tissue, and this event provokes a bound water increase, and consequently an augmented tendon dimension [ 13 ]. Tendon thickness is indeed moderately correlated with pain, for some authors [ 23 , 24 , 25 , 26 ], so it is considered as an indirect measure of treatment outcome [ 8 , 27 ]. Specifically, Romero C et al [ 28 ] found that an increase in Achilles tendon thickness and its cross-sectional area at 4 and 6 cm from the calcaneus, comparing subjects with and without Achilles tendinopathy.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound is the commonest examination for tendons and it considers primary three tendon features: (i) Thickness—tendinopathy can cause an increase in tendon thickness, due to a change in the number and type of cells of the tendon tissue, and this event provokes a bound water increase, and consequently an augmented tendon dimension [ 13 ]. Tendon thickness is indeed moderately correlated with pain, for some authors [ 23 , 24 , 25 , 26 ], so it is considered as an indirect measure of treatment outcome [ 8 , 27 ]. Specifically, Romero C et al [ 28 ] found that an increase in Achilles tendon thickness and its cross-sectional area at 4 and 6 cm from the calcaneus, comparing subjects with and without Achilles tendinopathy.…”
Section: Resultsmentioning
confidence: 99%
“…It has become the preferable modality for clinicians' screening and a valuable tool for researchers to compare and describe injured structures (14,15). US imaging has been found to be reliable and valid for evaluating Achilles tendon length, thickness, cross-sectional area, and the calcification length in patient with insertional Achilles tendinopathy (16)(17)(18)(19). However, validated and repeatable methods for evaluating the reliability of US imaging to quantify the insertional Achilles tendon size have yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Second, ultrasound examination was performed with only one machine to reduce the potential for measurement error; therefore, intermachine reliability could not be analyzed. Due to the large number of machines that are currently in use, intermachine reliability can be difficult to determine; however, intermachine reliability has been confirmed in sonographic measurements of tendon thickness, although it remains unclear for Morton neuromas. Further studies are needed to address the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%